KEPEMIMPINAN KEPALA SEKOLAH SEBAGAI PENGGERAK IMPLEMENTASI MANAJEMEN BERBASIS SEKOLAH DI SD NEGERI 1 KAPAL KABUPATEN BADUNG - Gede Agung, Anak Agung; Chindytia; Teja Mahotama, Ida Bagus; Diantari, I Gusti Ayu; Riska Dewi, Ni Kadek (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe and analyze the role of principal leadership as a driver of School-Based Management (SBM) implementation at SD Negeri 1 Kapal, Badung Regency, Bali. The study employed a descriptive qualitative approach with a case study design. Data were collected through in-depth interviews, direct observation, and document analysis, supported by SBM questionnaire tabulation from 30 teacher respondents in Cluster VI, Mengwi District. The results indicate that the principal practices inclusive transformational leadership, characterized by an open coordination culture, responsiveness to student needs, and participatory resource management. Three main leadership dimensions were identified: (1) driver of coordination and communication among school members; (2) driver of student management and special services; and (3) driver of a collaborative culture rooted in mutual cooperation. Questionnaire data showed SBM implementation achievement rates of 97.28% for curriculum management, 97.50% for student management, 98.18% for human resource management, and 100% for financial management. Principal leadership proved to be the key driver in creating a productive school ecosystem, although strengthening strategic documentation, data-based monitoring and evaluation, and the substantive role of the school committee are still needed for sustainable SBM optimization.